Association Between Fat Mass or Fat Fibrotic Gene Expression and Polyneuropathy in Subjects With Obesity: A Korean Metabolic Bariatric Surgery Cohort - Kim, Kyuho; Oh, Tae Jung; Park, Young Suk; Chang, Won; Cho, Hyen Chung; Lee, Jihye; Lee, Yun Kyung; Choi, Sung Hee; Jang, Hak Chul (Frontiers in Endocrinology, 2022)
Aim We aimed to investigate the association between obesity-related parameters and polyneuropathy (PN) and to evaluate inflammatory and fibrotic gene expression of fat as a potential mediator in subjects scheduled to undergo metabolic bariatric surgery (MBS). Methods This was a cross-sectional study of MBS cohort. Body composition and visceral fat area (VFA) were quantified by bioimpedance analysis and computed tomography scan. PN was defined by Michigan Neuropathy Screening Instrument–Physical Examination score was > 2. We measured mRNA expression level of FN1, TIMP1, CCL2, and CXCL8 in omental fat tissue. Results Of 189 subjects (mean age, 39.4 years; 69 [36.5%] male; mean body mass index, 38.5 kg/m2), prevalence of PN was 9.1% in subjects without diabetes (n = 110) and 20.3% in those with diabetes (n = 79). Nondiabetic subjects with PN had higher homeostatic model assessment-insulin resistance (6.8 ± 3.5 vs 4.5 ± 2.8, p = 0.041), and increased fat mass (58.5 ± 12.5 kg vs 50.5 ± 10.7 kg, p = 0.034), and VFA (309.4 ± 117.6 cm2vs 243.5 ± 94.2 cm2, p = 0.046) compared to those without PN. These obesity-related parameters were significantly associated with the presence of PN after adjusting for conventional risk factors of PN only in subjects without diabetes. In contrast, a fibrotic gene such as TIMP1 was independently associated with PN (adjusted odds ratio of 1.56; 95% confidence interval 1.06, 2.30) only in subjects with diabetes. Conclusion Increased adiposity was independently associated with PN in obese subjects without diabetes. In contrast, this association was not significant after adjusting conventional risk factors of PN in obese subjects with diabetes but increased fibrotic gene expression in fat was associated with PN in this group.